Organizational Transformation through Producers Participation : a Case Study of Producers Company - N. Balasubramani; S. Senthil Vinayagam (Journal of Agricultural Extension Management, 2014)
Indian agriculture has achieved self sufficiency in food production with the advancement of research and significant contribution of the extension system. However, the farmers are facing various challenges in marketing their produce and have yet to realize better farm gate price, despite various models initiated by the public as well as private sectors. One such model initiated by DPIP in Madhya Pradesh is Producer Company. A case study on a Producer Company (HAMPCO) has been undertaken to analyse the existing producer and market linkage mechanism, organizational systems, and functioning of the model and initiatives to enhance the profitability of the farmers. The study reveals that a Producer Company is owned by the community and managed by professionals. It is a good platform for convergence and a vehicle for transfer of technology, helps reduce cost of farm inputs and realize better farm prices. However, Government interventions may be required for sustaining the producers company during the initial stages